Vague Norm on HIV Status Disclosure of the Minister of Health Regulation Number 21 of 2013 - Putri, Idza Dean Akira Calluella; Firmantoro, Zuhad Aji (Dinasti Research, 2025)
Indonesia has produced various health laws in dealing with different infectious diseases. Treatment of HIV and AIDS, which includes infectious diseases, is regulated in Minister of Health Regulation Number 21 of 2013. In accordance with Minister of Health Regulation Number 21 of 2013, it is stated that PLWH must disclose their HIV status to their sexual partners. On the other hand, the provision stating that PLWH must disclose their HIV status to their family is still ambiguous, making it challenging to apply in the treatment of HIV and AIDS. This article examines the problem of vague norm with the existence of an ambiguous article on HIV status disclosure in Minister of Health Regulation Number 21 of 2013. This article uses a normative legal research method through a legislative approach and an analytical approach. The results show that vague norms in Minister of Health Regulation Number 21 of 2013 related to the treatment of HIV status by PLWH to their families creates legal uncertainty and hampers the effectiveness of the treatment of HIV and AIDS. The problem of legal certainty in disclosing HIV status must be resolved so that the treatment of HIV and AIDS can run optimally. The vagueness of the material in this regulation makes it difficult to be applied consistently. To overcome this, it is recommended that the law be improved so that the treatment of HIV and AIDS in Indonesia can run more optimally and achieve the goal of “three zero” by 2030.